PRÉ-TRATAMENTO DAS SEMENTES DO QUIABEIRO PARA ACELERAR E UNIFORMIZAR A GERMINAÇÃO - Gurgel, J. T. A. (REVISTA DE AGRICULTURA, 2016)
PRÉ-TRATAMENTO DAS SEMENTES DO QUIABEIRO PARA ACELERAR E UNIFORMIZAR A GERMINAÇÃO